Clinical and palliative care outcomes for patients of poor performance status treated with antiprogrammed death‐1 monoclonal antibodies for advanced melanoma. Issue 6 (29th June 2017) - Wong, Annie; Williams, Molly; Milne, Donna; Morris, Kortnye; Lau, Peter; Spruyt, Odette; Fullerton, Sonia; McArthur, Grant
Abstract: Background: Antiprogrammed death‐1 antibodies (anti‐PD1) have response rates of 40% in metastatic melanoma. Patients with poor performance status (PS) were excluded from clinical trials, yet use of anti‐PD1 is widespread in clinical practice. Literature regarding clinical and palliative care outcomes in patients with poor PS treated with anti‐PD1 is lacking. Methods: Retrospective review of outcomes for all patients with advanced melanoma treated with anti‐PD1 between 2012 and June 2015 at Peter MacCallum Cancer Centre, a tertiary specialist cancer center in Australia. Results: Between 2012 and 2015, 91 patients received anti‐PD1: median age 63, 65% males, 77% elevated LDH>1xULN (37/48 patients). Fifty‐eight patients had baseline ECOG PS of 0–1 (64%), 24 patients ECOG PS 2–3 (26%) and ECOG PS was not recorded in nine patients (10%). Median overall survival (OS) for the ECOG PS 0–1 group was 19.5 months and 1.8 months for ECOG PS 2–3 (HR 5.5; 95% CI, 9.1–50.3; P = 0.0001). Tumor response was 23/58 (39%) in ECOG PS 0–1, 2/16 (12%) in ECOG PS 2 and 0/8 in ECOG PS 3. Toxicity did not differ between different groups. ECOG PS 2–3 patients were more likely to be treated and hospitalized within the last month of life compared to ECOG PS 0–1 patients, RR 1.75 (95% CI, 1.04–2.56, P = 0.019) and RR 1.73 (95% CI, 1.10–2.16, P = 0.009), respectively. ECOG PS 2–3 patients were more likely to die in an acute hospital RR 2.68 (95% CI, 1.17–6.51, P = 0.016). Conclusions: Patients with poor baseline PS have a significantly lower OS and reduced response to anti‐PD1. Further quality of life and palliative care research is needed.